Are maternal and child health initiatives helping to reduce under-five mortality in Ghana? Results of a quasi-experimental study using coarsened exact matching - Augusta Kolekang; Bismark Sarfo; Anthony Danso-Appiah; Duah Dwomoh; Patricia Akweongo (BMC, 2021)
Abstract Background Despite a 53 % decline in under-five mortality (U5M) worldwide during the period of the Millennium Development Goals (MDGs), U5M remains a challenge. Under-five mortality decline in Ghana is slow and not parallel with the level of coverage of child health interventions. The interventions promoted to improve child survival include early initiation of breastfeeding, clean postnatal care, and skilled delivery. This study sought to assess the effectiveness of these interventions on U5M in Ghana. Methods A quasi-experimental study was conducted using secondary data of the 2008 and 2014 Ghana Demographic and Health Surveys. Coarsened Exact Matching and logistic regression were done. The interventions assessed were iron intake, early initiation of breastfeeding, clean postnatal care, hygienic disposal of stool, antenatal care visits, skilled delivery, intermittent preventive treatment of malaria in pregnancy, and tetanus toxoid vaccine. Results There were 2,045 children under-five years and 40 (1.9 %) deaths in 2008. In 2014, the total number of children under-five years was 4,053, while deaths were 53(1.2 %). In 2014, children less than one month old formed 1.6 % of all children under-five years, but 47.8 % of those who died. Mothers who attended four or more antenatal care visits were 78.2 % in 2008 and 87.0 % in 2014. Coverage levels of improved sanitation and water connection in the home were among the lowest, with 11.6 % for improved sanitation and 7.3 % for water connection in the home in 2014. Fifty-eight (58), 1.4 %, of children received all the eight (8) interventions in 2014, and none of those who received all these interventions died. After controlling for potential confounders, clean postnatal care was associated with a 66% reduction in the average odds of death (aOR = 0.34, 95 %CI:0.14-0.82), while early initiation of breastfeeding was associated with a 62 % reduction in the average odds of death (aOR = 0.38, 95 % CI: 0.21-0.69). Conclusions Two (clean postnatal care and early initiation of breastfeeding) out of eight interventions were associated with a reduction in the average odds of death. Thus, a further decline in under-five mortality in Ghana will require an increase in the coverage levels of these two high-impact interventions.